An Uncommon Presentation of Pigmented Paravenous Retinochoroidal Atrophy - Bhakhri, Raman; Patel, Kevin (Canadian Journal of Optometry, 2024)
Pigmented paravenous retinochoroidal atrophy is a rare diagnosis of exclusion as it can mimic many hereditary retinal (namely retinitis pigmentosa), infectious, and inflammatory disorders. Once diagnosed, it carries a favorable prognosis due to the macula being spared with slow to no progression and lack of symptoms. However, rare cases have noted macula involvement and symptoms including nyctalopia. Clinicians should be aware of presentations of pigmented paravenous retinochoroidal atrophy, beyond the typical findings noted in the literature, as these cases could be misdiagnosed. This case presents a rare presentation of pigmented paravenous retinochoroidal atrophy. A review of common and uncommon findings, potential pathophysiology, differential diagnoses, and multimodal imaging results is also presented.